2020
DOI: 10.1101/2020.10.09.333229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome-scale assembly of the genome ofSalix dunniireveals a male-heterogametic sex determination system on chromosome 7

Abstract: Sex determination systems in plants can involve either female or male heterogamety (ZW or XY, respectively). Here we used Illumina short reads, Oxford Nanopore Technologies (ONT) long reads, and Hi-C reads to assemble the first chromosome-scale genome of a female willow tree (Salix dunnii), and to predict genes using transcriptome sequences and available databases. The final genome sequence of 328 Mb in total was assembled in 29 contigs, and includes 31,501 genes. We inferred a male heterogametic sex determini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 119 publications
2
8
0
1
Order By: Relevance
“…A recent study analyzed differences in sex determination systems in subg. Salix and the Chamaetia/Vetrix clade, which might be responsible for incompatibilities between the two subgeneric clades (He et al, 2021a). This would support our conclusion that the plastomes of the subgenera evolved more independently.…”
Section: Molecular Dating Opposed Hypotheses Of Rapid Radiation or Rapid Range Expansion From Refugiasupporting
confidence: 83%
“…A recent study analyzed differences in sex determination systems in subg. Salix and the Chamaetia/Vetrix clade, which might be responsible for incompatibilities between the two subgeneric clades (He et al, 2021a). This would support our conclusion that the plastomes of the subgenera evolved more independently.…”
Section: Molecular Dating Opposed Hypotheses Of Rapid Radiation or Rapid Range Expansion From Refugiasupporting
confidence: 83%
“…In this study, we identified and assembled the SDRs of two additional Salix species. Salix chaenomeloides has an XY SDR on chr7, which is in a similar location as a previously described SDR in S. nigra [29] and S. dunnii [52]. All three of these species are in subgenus Protitea [57].…”
supporting
confidence: 83%
“…In contrast, sex determination regions (SDRs) were previously identified on chr15 with a ZW system in multiple willow species of subgenus Vetrix (including S. purpurea, S. viminalis and S. suchowensis) [54,55,57,58] and S. triandra of subgenus Salix [59], until the recent identification of the XY system on chr7 of two willow species from subgenus Protitea (S. nigra and S. dunnii) (Fig. 1A) [29,52].…”
mentioning
confidence: 98%
See 2 more Smart Citations